THEORETICAL CONCEPTS OF DETERMINATION OF PSYCHOSOMATIC DISORDERS: FROM THEORY TO PRACTICE - Mirzoyan, Vanane (Modern Psychology, 2025)
In recent years, the number of patients suffering from psychosomatic disorders has sharply increased, as evidenced by both doctors, psychologists and psychotherapists.Psychosomatic disorders are complex and multifaceted phenomena, which are based on both psychological and somatic processes. Historically, various researchers have proposed many models and concepts in an attempt to explain the relationship between mental states and physical symptoms. So, for example, in the 5th century BC, Socrates argued that there is no physical illness separate from the mental, and Plato said: “A big mistake is made where physical and mental illnesses are treated by different doctors. After all, the body is inseparable from the soul.” Hippocrates considered illness not a punishment from the gods, but a violation of hygiene rules, the result of an incorrect lifestyle and environmental conditions. If doctors believe that the causes of the disease are factors such as genetics, viruses, bacteria and other biological factors, psychotherapists assign an important role to psychological factors: a person’s lifestyle, his experiences, psycho-emotional state.  The purpose of this article is to study psychological factors in the formation and occurrence of psychosomatic disorders. Key psychoanalytic, characterological, neurophysiological, and integrative theories that have helped lay the foundations for understanding psychosomatic disorders are reviewed.
Keywords: psychosomatic disorders; determination of disorders; emotion; disease; gestalt approach